Penyuluhan terapi pijat wajah untuk mengatasi gerakan tutup mulut pada balita - Marice Marice; Therecia Wijayati; Youlenta Ernesonta; Intan Intan; Elsa Elsa; Cristianingsih Sri Paninggih (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The behavior of keeping the mouth closed (refusing food) in toddlers is an issue that can affect feeding, communication, and the development of oromotor function. One non-pharmacological intervention involves educating parents on facial massage techniques to stimulate facial muscles and help improve oral movement function. Purpose: To enhance parents' knowledge and skills in performing facial massage to help address the issue of toddlers keeping their mouths closed (refusing food). Method: This activity was conducted on February 24, 2026, at the Pal III Community Health Center (Puskesmas) in Sungai Jawi Urban Village, Pontianak City District, West Kalimantan. The study involved 77 mothers of toddlers as respondents. The initiative aimed to empower mothers through education on complementary care specifically facial massage to address this refusal behavior. Respondents' knowledge and understanding were assessed using a one-group pretest-posttest design, with questionnaires administered before and after the educational session. Skill levels were evaluated through observation of practical simulations using anatomical models (phantoms). Evaluation involved analyzing the aggregated questionnaire data and descriptively reporting the results regarding the achievement and improvement of respondents' knowledge concerning the benefits of facial massage for this issue. Results: The study showed that the mean age of respondents was 32.3 years, with the majority (50.6%) falling within the 20–29 age range. Evaluation results indicated an increase in participants' knowledge regarding the benefits of facial massage for toddlers experiencing